2023
DOI: 10.1177/00469580231172879
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Correlates, and Trends of Intimate Partner Violence Against Women in Gambia: Results From 2 National Cross-Sectional Health Surveys

Abstract: No country is immune from intimate partner violence (IPV). The objectives of this study were to analyze the prevalence, correlates and trends of this global public health menace perpetrated by men against women using the most recent nationally representative Gambia Demographic and Health Survey (GDHS) 2019-20; with analysis of levels and trends of IPV perpetrated by current/former husbands/partners from ever-married women, from GDHS conducted in 2013, at the 8 subnational regions. IPV association with 12 covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…There is a contrast with the global and WHO Africa Region estimates of physical and/or sexual IPV in a similar demographic, which in 2018 were 27 and 33%, respectively ( 3 ); the victimization and resultant harm among Sierra Leonean women exceeded the global average by 24.67 percentage points and that of the WHO Africa Region by 18.67 percentage points. Among the three types of IPV, the lifetime prevalence of physical IPV was the highest, which is a finding in consonance with other studies ( 20 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is a contrast with the global and WHO Africa Region estimates of physical and/or sexual IPV in a similar demographic, which in 2018 were 27 and 33%, respectively ( 3 ); the victimization and resultant harm among Sierra Leonean women exceeded the global average by 24.67 percentage points and that of the WHO Africa Region by 18.67 percentage points. Among the three types of IPV, the lifetime prevalence of physical IPV was the highest, which is a finding in consonance with other studies ( 20 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…Occupational status, residential status, and decision-making participation were not statistically significantly associated with IPV. A recent study from Gambia also reported a similar lack of statistically significant association with IPV via bivariate analysis using the DHS data ( 26 ), contrasting with the recent meta-analysis that reported the association of residency in rural areas with IPV ( 5 ).…”
Section: Discussionmentioning
confidence: 76%
“…However, the cross-sectional design of DHS does not render any causal inferences, merely associations. Such association between controlling behavior and high IPV has been reported previously [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…In general rural denizens tend to have lower educational attainment, economic status, and more pronounced patriarchal societies. Yet, this lack of association might reflect IPV pervasiveness, but such lack of association has also been previously reported [ 24 , 28 ]. While results of multivariable analyses showed the statistically significant associations of IPV with the number of living children; partner’s use of alcohol; having knowledge of IPV at home; and marital control.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation